(untitled) ("Temas Sociais" Journal, 2024)
This research aims to understand the importance of performance evaluation and management in motivating employees. The study was carried out in the Unidade de Cuidados Continuados Integrados of the Santa Casa da Misericórdia de Vila de Rei through a mixed methodology, using different methods of data collection: in the qualitative approach, a semi-structured interview with the technical director was used, whose function is managing people; and in the quantitative approach, a closed-type questionnaire to 58 of the organization’s 63 employees was applied. The interview and the questionnaire are both divided into the research themes: People Management, Motivation Factors at Work, Performance Evaluation, and Performance Evaluation and Management. The results show that the UCCI employees consider the following factors as the most critical contributors to their motivation: the excellent relationship with colleagues, the salary reward as extrinsic factors, and the personal growth and personal achievement as intrinsic factors. The employees and the technical director consider that performance evaluation is a motivating factor, that performance evaluation and management are essential processes, and that, when implemented in the UCCI, they would be a motivating factor.